KANDUNGAN ENERGI METABOLIS SEMU PAKAN DAN ENERGI METABOLIS SEMU TERKOREKSI N PADA GANDUM DENGAN SUPLEMENTASI ENZIM SEBAGAI SUBSTITUSI JAGUNG - Sandha Octavia; Irfan H. Junaidi; Eko Widodo (JURNAL ILMIAH PETERNAKAN TERPADU, 2017)
Feed broiler is one important factor that is very supportive of other factors when broiler maintenance. One way to reduce the use of maize is to use alternative raw materials of wheat. Wheat can be obtained and the price is cheaper than corn but contains a high Non Starch Polysaccharide, while the poultry digestive tool is not able to digest such crude fiber because it has no crude fiber-breaking enzymes so it needs enzyme addition to the efficient use of nutrient feed. The research method used is the experimental method using Completely Randomized Design consisting of 4 treatments 5 replications. The treatment is as follows P0 (without wheat and xylanase); P1 (substitution of maize with 20% wheat); P2 (maize substitution with 40% wheat) and P3 (substitution of maize with 60% wheat). The observed variables are metabolic energy of pseudo-feed and metabolically correlated false energy n. Data were analyzed by analysis of variance (ANOVA) if there are differences among the treatments followed by Duncan's Test. The results showed that the use of wheat with a xylanase enzyme supplementation as a substitute corn provides highly significant effect (P<0.01) on the apparent metabolize energy of feed and apparent metabolize energy corrected N. The addition of xylanase enzymes in feed with the substitution of wheat by 20 percent produce the best feed metabolizable energy among other treatments.  Keywords : Broiler, Wheat, Enzymes, Energy, Feed